James Monroe papers - Monroe, James, 1758-1831.
Correspondence relating primarily to negotiations for the Louisiana Purchase, the Monroe-Pinkney treaty with Great Britain (1807), the War of 1812, the purchase of Florida, South American independence, and Virginia politics; diary (1825 Feb.); account book containing memoranda and official and personal accounts (1794-1802); and other papers. Correspondents include John Adams, John Quincy Adams, John Armstrong, Joel Barlow, William Benton, James Bowdoin, John C. Calhoun, William Harris Crawford, Henry Dearborn, Thomas Erskine, George William Erving, Albert Gallatin, John Graham, Richard H. Henderson, David Humphreys, Andrew Jackson, Thomas Jefferson, Joseph Jones, Rufus King, Thomas Law, Robert R. Livingston, James Madison, John McLean, John Francis Mercer, William Pinkney, Edmund Randolph, John Randolph, Spencer Roane, C. A. Rodney, Richard Rush, John Taylor, Littleton Waller Tazewell, St. George Tucker, George Washington, and William Wirt.
Microfilm edition of Series 1-3 available
Microfilm produced from originals in the Manuscript Division.
Microfilm edition of originals in private hands available
Microfilm of originals in private hands.
Private
In part, photocopies.
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Adams, John Quincy, -- 1767-1848 -- Correspondence; Armstrong, John, -- 1758-1843 -- Correspondence; Barlow, Joel, -- 1754-1812 -- Correspondence; Benton, William, -- 1788-1881 -- Correspondence; Bowdoin, James, -- 1752-1811 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Crawford, William Harris, -- 1772-1834 -- Correspondence; Dearborn, Henry, -- 1751-1829 -- Correspondence; Erskine, Thomas Erskine, -- Baron, -- 1750-1823 -- Correspondence; Erving, George William, -- 1769-1850 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Graham, John, -- 1774-1820 -- Correspondence; Henderson, Richard H., -- active 1822 -- Correspondence; Humphreys, David, -- 1752-1818 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Jones, Joseph, -- 1727-1805 -- Correspondence; King, Rufus, -- 1755-1827 -- Correspondence; Law, Thomas, -- 1756-1834 -- Correspondence; Livingston, Robert R., -- 1746-1813 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; McLean, John, -- 1785-1861 -- Correspondence; Mercer, John Francis, -- 1759-1821 -- Correspondence; Pinkney, William, -- 1764-1822 -- Correspondence; Randolph, Edmund, -- 1753-1813 -- Correspondence; Randolph, John, -- 1773-1833 -- Correspondence; Roane, Spencer, -- 1762-1822 -- Correspondence; Rodney, C. A. -- 1772-1824 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Taylor, John, -- 1753-1824 -- Correspondence; Tazewell, Littleton Waller, -- 1774-1860 -- Correspondence; Tucker, St. George, -- 1752-1827 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Wirt, William, -- 1772-1834 -- Correspondence; Louisiana Purchase; Florida -- History -- Spanish colony, 1784-1821.; France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; Great Britain -- Foreign relations -- Treaties; South America -- History -- Wars of Independence, 1806-1830.; Spain -- Foreign relations -- United States; United States -- Foreign relations -- 1783-1865.; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; United States -- Foreign relations -- Spain; United States -- Foreign relations -- Treaties; United States -- History -- 1783-1865.; United States -- History -- War of 1812.; United States -- Politics and government -- 1817-1825.; Virginia -- Politics and government; Cabinet officers; Delegates, U.S. Continental Congress -- Virginia; Diplomats; Presidents -- United States